2012
DOI: 10.1088/0004-637x/748/2/77
|View full text |Cite|
|
Sign up to set email alerts
|

EVOLUTION OF MAGNETIC FIELD AND ENERGY IN A MAJOR ERUPTIVE ACTIVE REGION BASED ONSDO/HMI OBSERVATION

Abstract: We report the evolution of magnetic field and its energy in NOAA active region 11158 over 5 days based on a vector magnetogram series from the Helioseismic and Magnetic Imager (HMI) on board the Solar Dynamic Observatory (SDO ). Fast flux emergence and strong shearing motion led to a quadrupolar sunspot complex that produced several major eruptions, including the first X-class flare of Solar Cycle 24. Extrapolated non-linear force-free coronal fields show substantial electric current and free energy increase d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
382
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(470 citation statements)
references
References 71 publications
82
382
6
Order By: Relevance
“…Around the PIL, there are some observed EUV loops connecting P2 with N1. Our extrapolation has obtained a series of small and low calculated magnetic field lines along the PIL and connecting the regions on both sides, which are agreeable with the EUV loop structures in general and the filament structure marked in Figure 1 in Sun et al (2012), as shown in the last two rows in Figure 7. However, we did not obtain higher-lying calculated magnetic field lines over the filament channel connecting footpoints with opposite magnetic polarities P2 and N1.…”
Section: Reconstructed Resultssupporting
confidence: 81%
“…Around the PIL, there are some observed EUV loops connecting P2 with N1. Our extrapolation has obtained a series of small and low calculated magnetic field lines along the PIL and connecting the regions on both sides, which are agreeable with the EUV loop structures in general and the filament structure marked in Figure 1 in Sun et al (2012), as shown in the last two rows in Figure 7. However, we did not obtain higher-lying calculated magnetic field lines over the filament channel connecting footpoints with opposite magnetic polarities P2 and N1.…”
Section: Reconstructed Resultssupporting
confidence: 81%
“…Local changes in the horizontal photospheric magnetic fields were also recently reported (e.g. Wang et al 2002;Sun et al 2012;Wang et al 2012;Petrie 2013), while in those studies, the vertical field component does not change much.…”
Section: Electric Currents In Observations and Their Associations Wisupporting
confidence: 61%
“…In more recent years, high-resolution white-light sunspot observations revealed some changes in photospheric fine structures caused by flares, e.g., disappearing penumbra fibrils and transition bright grains could evolve into faculae (Wang et al 2012a), granulation pattern could evolve to alternating dark and bright penumbra fibril structures (Wang et al 2013), and there were remarkable high-speed flows along the flaring PILs (Shimizu et al 2014). On the other hand, the photospheric vector magnetic-field observations showed that the horizontal magnetic fields increased rapidly and permanently around the central PILs (Wang & Liu 2010;Liu et al 2012;Petrie 2012;Sun et al 2012;Wang et al 2012bWang et al , 2012c, while they decreased significantly in the outer regions (Wang et al 2009;Li et al 2011;Sun et al 2012). These results thus suggested that, after major flares, the magnetic fields often became more horizontal in the central PIL regions but more vertical in the decaying penumbra regions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the LF changes can be understood as a proxy for the pressure changes from the upper atmosphere to the photosphere. More recently, it was found that during major flares the sudden photospheric magnetic structure changes in their central regions close to the main flaring PILs might have been accompanied by obvious LF changes, such as the downward LF changes Petrie 2012;Sun et al 2012;Wang et al 2012bWang et al , 2012c, the horizontal LF changes providing torque for rapid sunspot rotation (Wang et al 2014) or abrupt torsional force for relaxing magnetic twist near the PILs (Petrie 2013), and so on. Besides the central regions, as mentioned above, the peripheral penumbra regions can decay clearly in some major flares.…”
Section: Introductionmentioning
confidence: 99%